Impact of interleukin 13 (IL13) genetic polymorphism Arg130Gln on total serum immunoglobulin (IgE) levels and interferon (IFN)-γ gene expression. (7th February 2017) - Smolkova, B; Tulinska, J; Palkovicova Murinova, L; Buocikova, V; Liskova, A; Rausova, K; Kuricova, M; Patayova, H; Sustrova, M; Neubauerova Svorcova, E; Ilavska, S; Szabova, M; et al.
Summary: This cross-sectional study was designed to investigate the extent of genetic susceptibility by targeting variants in interleukin (IL)−4/IL-13 signalling pathways leading to atopic disease in early childhood. We evaluated involvement of five single nucleotide polymorphisms IL4 C-590T, IL13 C-1055T, IL13 Arg130Gln, IL4RA Ile50Val and IL4RA Gln576Arg, in the control of serum total and antigen-specific immunoglobulin (Ig)E levels. Furthermore, we analysed their association with changes in gene expression of five cytokines having key roles in inflammatory and anti-inflammatory immune response [IL-4, IL-13, interferon (IFN)-γ, IL-8 and IL-10]. Total and antigen-specific IgE levels in serum and gene expression of selected cytokines in peripheral blood were measured in 386 children aged 1–8 years. TaqMan allelic discrimination, amplification refractory mutation system–polymerase chain reaction (ARMS–PCR) and restriction fragment length polymorphisms (RFLP) methods validated by sequencing were used for genotyping. All genotypes for children with total and antigen-specific IgE levels in the normal range were in Hardy–Weinberg equilibrium. Gene expression analyses were carried out using TaqMan gene expression assays. We found elevated total IgE levels in carriers of IL13 Arg130Gln variant allele [odds ratio (OR) = 1·84; 95% confidence interval (CI) = 1·16-2·93]. This effect was more apparent for boys (OR = 2·31; 95% CI = 1·25-4·28). However, no significant association was observed for the other four variants examined. We found up-regulation of IFN-γ in children with elevated serum total IgE levels carrying the Arg130 allele ( P  = 0·005). No differences were found for IL4, IL8 or IL10, while IL13 gene expression was under the detection limit. IL13 Arg130Gln genotypes can play a role in genetic susceptibility to allergy via regulation of serum total IgE levels and affecting IFN-γ gene expression. Graphical Abstract: